Assessment of diastolic function in elderly patients with aortic stenosis. Evaluation of flow propagation velocity using color M-mode Doppler technique - Nobuoka, Sachihiko; Suzuki, Kengo; Imai, Yukiko; Adachi, Hisanobu; Shibamoto, Masaaki; Yoshida, Akihiro; Miyake, Fumihiko; Nakamura, Toshio (Geriatrics & gerontology international, 2005)
Background:  The purpose of this study was to assess the left ventricular (LV) diastolic function in elderly patients with aortic stenosis (AS). Methods:  The subjects included 11 consecutive elderly patients with AS (AS group), and 17 elderly patients with hypertensive LV hypertrophy (HT group), all were more than 70 years of age. Echocardiographic and Doppler examinations were performed, and the data was analyzed to determine the LV end‐diastolic dimension (LVDd), the LV mass index (LVMI), fractional fiber shortening (FS), the aortic valve resistance (AVR), peak aortic flow velocity (peak V), and the maximal early diastolic transmitral flow velocity (E). The flow propagation velocity (FPV) was measured during early LV filling phase using a color M‐mode Doppler method. Then, (i) FPV/E were compared between the two groups; and (ii) correlations between FPV/E and LVMI, LVDd, AVR, and FS/peak V were assessed in the AS group. Results:  FPV/E was significantly lower in the AS group than in the HT group (P < 0.01). There were significant negative correlations between FPV/E and LVMI (r =−0.728, P < 0.001), and FPV/E and LVDd (r =−0.642, P < 0.01) in the AS group. There were no significant correlations between FPV/E and AVR, and FPV/E and FS/peak V. Conclusion:  We considered that in elderly patients with AS, diastolic dysfunction was more severe than that of hypertensive heart disease even if the LV hypertrophy is equivalent, and diastolic dysfunction was more severe in cases having a larger LVDd and a larger LVMI, and could not be related to hemodynamic severity of AS.